The human icon: Gregory of Nazianzus on being an imago Dei - Thomas, Gabrielle (Scottish journal of theology, 2019)
Theologians have long recognised the significance of the imago Dei in Christian theological anthropology, yet the question of how to construe the imago is not straightforward. This essay offers a fresh reading of Gregory Nazianzen's vision of the imago Dei. Hitherto, historical theologians have attributed to Gregory an essentialist interpretation of the imago, in which it is identified only with the rational soul. I argue that Gregory depicts the imago Dei quite literally as a visible icon of God by weaving together christology, pneumatology and beliefs about images and idols. If interpreted properly, Gregory's vision contributes significantly to contemporary interpretations of the imago Dei, which aim to account for christology, pneumatology and the inclusion of each human person in the imago.